The rise in teenagers skipping school across English speaking countries. Evidence from PISA. - Anders, Jake; Jerrim, John; Ladrón de Guevara Rodríguez, Maria; Marcenaro-Gutiérrez, Óscar David (Springer, 2025)
Many countries are grappling with the long shadow that COVID has cast over their education systems, including dramatic increases in absence from school. This paper presents new insights into this issue by investigating how the proportion of teenagers skipping school has changed following the COVID-19 pandemic across the developed world. We find that this problem is mainly confined to industrialised English-speaking nations, especially affecting teenage girls. In contrast, the proportion of 15-year-olds skipping school remains similar to pre-pandemic levels in most other members of the OECD. Counter to much of the previous literature on COVID-induced learning loss, we find no evidence of a link between student truancy and length of school closures. Our results do highlight, however, that English-speaking nations risk falling behind their international competitors unless radical action is taken to reduce the growing number of teenagers regularly skipping school.
Keywords: COVID-19 - Influencia y consecuencias; Educación - Modelos matemáticos; Absentismo escolar; Truancy; COVID-19; School closures; PISA; Skipping school